Організація внутрішьогосподарського контролю в умовах воєнного стану - Павлова, Галина Євгеніївна; Pavlova, Halyna; Атамас, Олександр Петрович; Atamas, Oleksandr; Вінніченко, Наталія Юріївна; Vinnichenko, Nataliia (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
Внаслідок введення воєнного стану в Україні було порушено порядок ведення бухгалтерського обліку та внутр-ішньогосподарського контролю, особливо структурних елементів активів та підприємств, які формуються в цілому. Деякі з підприємств були зруйновані або пошкоджені; частина з них залишилася на тимчасово окупованих територіях, а решта майна була або захоплена, або вивезена силою. Слід зазначити, що постає питання про необхідність запровадження ефективного внутрішньогосподарського контролю. Визначено, що внутрішньогосподарський контроль за ключовою роль в управлінні підприємством забезпечує перевірку ефективності реалізації управлінських рішень, виявлення та усунення відхилень у фінансово-господарській діяльності та системі обліку, а також контроль за станом і використанням матеріальних ресурсів та активів підприємства. Він включає систему спостережень та перевірок, що оцінює відповідність діяльності підприємства, прийнятим рішенням із застосуванням об'єктивного аналізу ефективності діяльності, законності господарських операцій, збереження власності, достовірності звітності, а також виявлення внутрішніх резервів. Currently, a reliable internal control system supports the role of a reserve for improving management efficiency, which reduces the company's costs and creates conditions for its further development. Implementation of controls on enterprises is the ultimate goal to be achieved. Sometimes, in ensuring the effective use of resources to achieve the whole work and material measures used to obtain results are of much greater importance than the results obtained. The question arises about the need to introduce effective internal economic control. This question arises in connection with the relevance of the research and a number of problematic issues for many Ukrainian accountants regarding the organization of internal economic control at enterprises during the war in Ukraine. In the conditions of total war, when accounting is conducted through an uninterrupted continuous record of all economic transactions, it becomes difficult. Its purpose is to record and summarize data on the state of assets, liabilities and equity of the enterprise. During the martial law, many accounting principles and methods were changed, which hada negative impact on the internal economic discipline of the enterprise. Improving the organization of internal control is motivated by: increasing the level of trust on the part of business partners, reduction of entrepreneurial risk. As a result of the study of the system of internal economic control at enterprises, it can be concluded that little attention is paid to regulatory support and its quality: establishment of job instructions, rules and performance of control functions in them. It is worth noting that despite the urgency of the issue, the establishment of an effective internal control system remains unresolved at many enterprises. Weaknesses in the organization often lead to significant financial losses. At the same time, an enterprise that pays due attention to the internal control system achieves better results in its activities. More and more managers are beginning to realize the importance of quality control. The conducted research showed that the issue of internal control at Ukrainian enterprises, especially in the conditions of armed aggression, needs improvement both at the legislative level and in organizational and methodological aspects.
Organization of domestic economic control under the conditions o f marital state
Keywords: організація; organization; бухгалтерський облік; accounting; внутрішньогосподарський контроль; intra-economic control; воєнний стан; martial law; удосконалення; improvement